Penerapan Model PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Perbandingan dan Skala Kelas V SD - Nafia, Dwi; Ahmad, Syafri; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to improve the problem solving ability of comparisons and scales through the application of Problem Based Learning (PBL) model. This study was a classroom action research that conducted in two cycles. The subject of this study was the fifth grade students of SD Negeri 13 Simpang Haru Padang City 2017/2018 Academic Year which consisted of 26 students. The data collected were through observation and test. The results of this study indicated that the application of the Problem Based Learning (PBL) model could improve problem-solving ability, namely from cycle 1 to cycle II by 10.21% from with very good criterion. If could be concluded that the Problem Based Learning (PBL) model could improve problem solving ability of comparison and scale material